Pengaruh teknologi informasi terhadap kinerja keuangan melalui mekanisme transaction cost di institusi kesehatan - Rianawati, Andri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study examines the effect of the use of information technology (IT) on the financial performance of health institutions through the transaction economic mechanism. The use of IT is increasing, especially during the Covid-19 pandemic. The use of IT affects the transaction cost process in an organization. Transaction cost theory focuses on exchange processes that incur costs. This study uses quantitative methods with online survey data collection. Hypothesis testing was carried out using the structural equation modeling (SEM) test with SmartPLS 3.3.9. The test results show that the use of IT has a negative effect on transaction costs, the second is that transaction costs have a negative effect on financial performance, and the last is that IT has a positive effect on financial performance. This research has theoretical and practical contributions. The theoretical contribution is to increase literacy related to transaction costs in the context of health institutions. While the practical contribution is to provide knowledge related to transaction costs in improving the financial performance of health institutions.